Ultrasound-guided thermal ablation versus laparoscopic surgery for focal nodular hyperplasia of the liver: A retrospective controlled study - Zhang, Dan-ling; Chen, Sheng; Lin, Yu-cheng; Ye, Wenxin; Li, Kai; Wu, Song-song (Frontiers in Oncology, 2022)
Purpose This study aims to evaluate the value of the clinical application of ultrasound-guided percutaneous thermal ablation in focal nodular hyperplasia (FNH) by comparing its safety, effectiveness, and patient experience to surgery in the treatment of hepatic FNH ≤5 cm. Method This retrospective study enrolled 82 patients with hepatic FNH having a maximum diameter of ≤5 cm, confirmed by postoperative pathologic diagnosis or needle biopsy, who underwent thermal ablation or surgery between January 2019 and September 2021. Postoperative efficacy, surgical trauma (operation time, intraoperative bleeding volume, liver function, and lost volume of normal liver tissue), postoperative complications (postoperative infection, pleural effusion, and liver dysfunction), patient experience (degree and time of postoperative pain, postoperative fasting time, indwelling thoracic chest drain, and scar size), and economic indices (postoperative hospitalization and total charges) were compared between both groups. Result No significant difference existed in postoperative efficacy between both groups (p > 0.05). No recurrent or new lesions were observed during the 6-month follow-up in both groups. However, significant differences were observed in operation time, intraoperative bleeding volume, and lost volume of normal liver tissue (p < 0.05), with significantly less trauma in the thermal ablation group. No statistically significant differences in ALT, AST, and Hb existed between both groups (p > 0.05); however, albumin was higher in the ablation group compared to the surgery group (38.21 ± 3.32 vs. 34.84 ± 3.71 g/L, p < 0.05), and WBC were lower in the ablation group (11.91 ± 3.37 vs. 13.94 ± 3.65/L, p < 0.05). The incidence of postoperative complications in the ablation group was significantly lower than that in the surgery group (p < 0.05). Patient experiences were significantly better than in the surgical group (p < 0.05), with economic indicators being significantly less in the ablation group (p < 0.05). Conclusion Ultrasound-guided percutaneous thermal ablation can treat hepatic FNH ≤5 cm with similar clinical efficacy as surgery and is an economical, safe, and minimally invasive treatment method worthy of recommendation.